a,4221:(x-15)=21
b,(6x-39):3).25=4956
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a
\(xy+3x-7y-21\\ =\left(xy+3x\right)-\left(7y+21\right)\\ =x\left(y+3\right)-7\left(y+3\right)\\ =\left(y+3\right)\left(x-7\right)\)
b
\(2xy-15-6x+5y\\ =\left(2xy-6x\right)-\left(15-5y\right)\\ =2x\left(y-3\right)-5\left(3-y\right)\\ =2x\left(y-3\right)+5\left(y-3\right)\\ =\left(y-3\right)\left(2x+5\right)\)
c Đề phải là \(\left(2x^2y+2xy^2-x-y\right)\) mới phân tích được: )
\(=2xy\left(x+y\right)-\left(x+y\right)\\ =\left(x+y\right)\left(2xy-1\right)\)
d
\(7x^3y-3xyz-21x^2+9z\\ =\left(7x^3y-21x^2\right)-\left(3xyz-9z\right)\\ =7x^2\left(xy-3\right)-3z\left(xy-3\right)\\ =\left(xy-3\right)\left(7x^2-3z\right)\)
e
\(4x^2-2x-y^2-y\\ =\left(2x\right)^2-y^2-\left(2x+y\right)\\ =\left(2x-y\right)\left(2x+y\right)-\left(2x+y\right)\\ =\left(2x+y\right)\left(2x-y-1\right)\)
f
\(9x^2-25y^2-6x+10y\\ =\left(3x\right)^2-\left(5y\right)^2-\left(6x-10y\right)\\ =\left(3x-5y\right)\left(3x+5y\right)-2\left(3x-5y\right)\\ =\left(3x-5y\right)\left(3x+5y-2\right)\)
a: =x(y+3)-7(y+3)
=(y+3)(x-7)
b: \(=2xy-6x+5y-15\)
=2x(y-3)+5(y-3)
=(y-3)(2x+5)
c: \(=2xy\left(x+y\right)-\left(x+y\right)=\left(x+y\right)\left(2xy-1\right)\)
d: \(=xy\left(7x^2-3z\right)-3\left(7x^2-3z\right)\)
=(7x^2-3z)(xy-3)
e: =4x^2-y^2-2x-y
=(2x-y)(2x+y)-(2x+y)
=(2x+y)(2x-y-1)
f: =(3x-5y)(3x+5y)-2(3x-5y)
=(3x-5y)(3x+5y-2)
b: =15/31(34/63-11/21)=15/31x1/63=5/651
a: \(=\dfrac{67}{63}\cdot5+\dfrac{11}{31}\cdot\dfrac{5}{7}=5\left(\dfrac{67}{63}+\dfrac{11}{31\cdot7}\right)=\dfrac{10880}{1953}\)
a)67/63 x 15/3 + 15/31 x 11/21
Thiếu đề
b)15/31 x 34/63 - 11/21 x 15/31
=15/31 x ( 34/63 -11/21)
= 15/31 x 1/63= 5/651
b: =15/31(34/63-11/21)=15/31x1/63=5/651
a: \(=\dfrac{67}{63}\cdot5+\dfrac{11}{31}\cdot\dfrac{5}{7}=5\left(\dfrac{67}{63}+\dfrac{11}{31\cdot7}\right)=\dfrac{10880}{1953}\)
b: =15/31(34/63-11/21)=15/31x1/63=5/651
a: =67/63⋅5+11/31⋅5/7=5(67/63+11/31⋅7)=10880/1953
(x-15):5+20=22
(x-15):5=22-20
(x-15):5=2
x-15=2x5
x-15=10
x=10+15
x=25
64+(20-3x)=75
20-3x=75-64
20-3x=11
3x=20-11
3x=9
x=9:3
x=3
[(6x-39):3].28=5628
(6x-39):3=5628:28
(6x-39):3=201
6x-39=201x3
6x-39=603
6x=603+39
6x=642
x=642:6
x=107
400-[545-(45+x)]=0
545-(45+x)=400-0
545-(45+x)=400
45+x=545-400
45+x=145
x=145-45
x=100
(111:x+25):14=2
111:x+25=2x14
111:x+25=28
111:x=28-25
111:x=3
x=111:3
x=37
a/ \(\Rightarrow\left(x-15\right):5=2\Rightarrow x-15=10\Rightarrow x=25\)
b/ \(\Rightarrow20-3x=11\Rightarrow3x=9\Rightarrow x=3\)
c/ => \(\left(6x-39\right):3=201\Rightarrow6x-39=603\Rightarrow6x=642\Rightarrow x=107\)
d/ \(\Rightarrow545-\left(45+x\right)=400\Rightarrow45+x=145\Rightarrow x=100\)
e/ \(\Rightarrow111:x+25=28\Rightarrow111:x=3\Rightarrow x=\frac{111}{3}\)
a,-4/7=x/21
-12/21 = x/21
x= -12
b,(x-3)/15=1/-5
x - 3 = -1/5 * 15
x - 3 = -3
x = 0
c,.(3x+8)/-12=-5/30
=> 3x + 8 = 2
=> 3x=-6
=>x=-2
a) 25 + 3x = 25 - 1
3x = -1
x = -1/3
b) (6x-39):13 = 201
6x-39 = 2613
6x = 2652
x = 442
c) 2x + 35:34 = 510 : 58
2x + 3 = 25
2x = 22
...
a: 2x-261=-21
=>\(2x=-21+261=240\)
=>\(x=\dfrac{240}{2}=120\)
b: \(15\cdot\left(-2\right)-x=45\)
=>-30-x=45
=>x=-30-45=-75
c: \(-18+\left(7-x\right)^2=-2\)
=>\(\left(x-7\right)^2-18=-2\)
=>\(\left(x-7\right)^2=-2+18=16\)
=>\(\left[{}\begin{matrix}x-7=4\\x-7=-4\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=11\\x=3\end{matrix}\right.\)
d: \(2x-1⋮x+1\)
=>\(2x+2-3⋮x+1\)
=>\(-3⋮x+1\)
=>\(x+1\inƯ\left(-3\right)\)
=>\(x+1\in\left\{1;-1;3;-3\right\}\)
=>\(x\in\left\{0;-2;2;-4\right\}\)
a,A=-(8a+21b-45)+(23a-11b-54)-(-32a-61b-11)
= -8a + 21b - 45 + 23a - 11b - 54 +32a -61b - 11
=47a - 51b - 110
b,B=-3(12a-21b+23)-4(-22a+15b-41)+(-11a-b+29)
=-36a + 63b - 69 + 88a - 60b + 164 - 11a - b + 29
=41a + 2b + 124
c,C=(-18a-43b+49)-2(54a-27b+25)+3(-15a+22b-17)
=-18a - 43b +49 - 108a + 54b - 50 - 45a + 66b - 51
=-171a + 77b - 52
Câu b có vấn đề nhé
2 ngoặc nhé